2000
DOI: 10.1055/s-2000-9008
|View full text |Cite
|
Sign up to set email alerts
|

Rectosigmoid Endometriosis: Endoscopic Ultrasound Features and Clinical Implications

Abstract: EUS is a simple and noninvasive technique capable of correctly diagnosing rectal wall infiltration in deep pelvic endometriosis. It may be helpful in determining the choice between laparoscopy and laparotomy when complete resection is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(78 citation statements)
references
References 16 publications
3
68
0
7
Order By: Relevance
“…Few data are available on the accuracy of endoscopic TRS for the diagnosis of uterosacral involvement. Roseau et al 18 reported that all such cases were accurately diagnosed using this imaging technique. However, Bazot et al 9 found that endoscopic TRS with high-frequency probes was less accurate for the diagnosis of uterosacral ligament involvement than was TVS with low-frequency probes that increase ultrasound penetration.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Few data are available on the accuracy of endoscopic TRS for the diagnosis of uterosacral involvement. Roseau et al 18 reported that all such cases were accurately diagnosed using this imaging technique. However, Bazot et al 9 found that endoscopic TRS with high-frequency probes was less accurate for the diagnosis of uterosacral ligament involvement than was TVS with low-frequency probes that increase ultrasound penetration.…”
Section: Discussionmentioning
confidence: 93%
“…Various imaging techniques have been used to diagnose endometriosis and to evaluate its extension in specific pelvic locations, such as the uterosacral ligaments, rectosigmoid, rectovaginal septum and bladder, with variable results 5,7,17,18 . In our experience, the sensitivity of TVS for the diagnosis of uterosacral ligament involvement is relatively low (70.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, the development of EUS has provided a brand new dimension in the diagnosis of colorectal lesions [5][6][7][8][9][10][11] . EUS can image the entire structure of the colonic wall which corresponds to the histologic layer structure.…”
Section: Discussionmentioning
confidence: 99%
“…Recto-sigmoid endometriosis may produce nonspecific symptoms such as diarrhea, rectal bleeding, and abdominal colic-like pain. This condition may require open surgery, and when the colon serosa is involved, meticulous dissection is required (3,4). Therefore, accurate preoperative imaging of recto-sigmoid involvement is important.…”
mentioning
confidence: 99%